Pasienttilfredshet i en avrusningsinstitusjon for pasienter med rusmiddelproblemer - en kvantitativ deskriptiv studie - Ask, Cathrine; Hanche-Olsen, Marte; Svindseth, Marit Følsvik (Nordisk Tidsskrift for Helseforskning, 2019)
Patient satisfaction in inpatient detoxification for substance use disorders - a quantitative descriptive studyThe primary purpose of the study is to discover important factors for patients at inpatient detoxification by studying patient satisfaction. Data were collected from a patient experience survey carried out from 2013-2015 at a detoxification unit in Norway. The study includes 185 responses (response rate 62 %). Data were analyzed with descriptive and inferential statistics. Significant associations were found between patients’ satisfaction and all the factors of the therapeutic relationship except respect and courtesy, support and motivation, which were non-significant in this study. Conversations with therapist showed the largest effect on patient satisfaction (effect size (ES) = 1.27), followed by conversations with doctor (ES = 0.78) and compassionate staff (ES = 0.52). The results suggest that the therapeutic relationship is associated with patient satisfaction in inpatient detoxification.